2016
DOI: 10.5194/bg-13-4945-2016
|View full text |Cite
|
Sign up to set email alerts
|

Wetland eco-engineering: measuring and modeling feedbacks of oxidation processes between plants and clay-rich material

Abstract: Abstract. Interest is growing in using soft sediment as a foundation in eco-engineering projects. Wetland construction in the Dutch lake Markermeer is an example: here, dredging some of the clay-rich lake-bed sediment and using it to construct wetland will soon begin. Natural processes will be utilized during and after construction to accelerate ecosystem development. Knowing that plants can eco-engineer their environment via positive or negative biogeochemical plant–soil feedbacks, we conducted a 6-month gree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The effect of plant richness on litter decomposition changed with drought intensity, which could be ascribed to a change in the sampling effect on litter nitrogen in response to the increase in drought intensity. While nitrogen was the main limiting element in our system, and in most ecosystems in the world, we need to be aware that phosphorous is the main limiting element in several other ecosystems such as some wetlands (Saaltink et al 2016;Saaltink et al 2017) and drylands (Lambers et al 2020). In such systems the dependence of litter decomposition on phosphorus should be put central studies of this kind.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of plant richness on litter decomposition changed with drought intensity, which could be ascribed to a change in the sampling effect on litter nitrogen in response to the increase in drought intensity. While nitrogen was the main limiting element in our system, and in most ecosystems in the world, we need to be aware that phosphorous is the main limiting element in several other ecosystems such as some wetlands (Saaltink et al 2016;Saaltink et al 2017) and drylands (Lambers et al 2020). In such systems the dependence of litter decomposition on phosphorus should be put central studies of this kind.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the higher the actual evapotranspiration of the plant species, the faster the suction recovery after a rainfall event for the same root biomass (Gaerg et al, 2015). Apart 25 from the drainage effect, vegetation also induces biogeochemical processes (Saaltink et al, 2016), which induce pedogenic processes that accelerate the maturation or ripening of the soil (e.g. Pons and Zonneveld, 1965;Barciela Rial et al, submitted).…”
Section: Comparison With Field Conditionsmentioning
confidence: 99%
“…Fast changes in the geochemical composition due to seasonal effects are not expected as the buffer capacities of these sediments are large (Saaltink et al 2016). From these sampling points, three sediment types were used: (1) the southern, well consolidated, Zuiderzee deposit of Holocene origin (10-50 cm depth), (2) the soft clayrich layer which is found on top of this deposit (0-10 cm depth), and (3) also a soft clay-rich layer at the northern part (0-10 cm depth).…”
Section: Experimental Designmentioning
confidence: 99%
“…To improve the ecological conditions, it is planned to dredge a part of the soft clay-rich lake-bed sediment and use this as a building material in constructing approximately 10,000 ha of wetland. In an earlier study, Saaltink et al (2016) found that the soft, clay-rich layer contains significant amounts of pyrite (FeS 2 ) and iron-bound phosphorus and they hypothesized that the main bottleneck preventing prompt development of ecosystems within the newly constructed wetland sites could be a form of iron toxicity. High belowground production of pioneering vegetation is especially important when using vegetation as ecological engineers for building these wetlands from soft mud, as roots have stabilizing capabilities, reduce erosion, and will increase the consolidation process.…”
Section: Introductionmentioning
confidence: 99%